Clinical spectrum of psychogenic non epileptic seizures in children; an observational study. (July 2018) - Madaan, Priyanka; Gulati, Sheffali; Chakrabarty, Biswaroop; Sapra, Savita; Sagar, Rajesh; Mohammad, Akbar; Pandey, R.M.; Tripathi, Manjari
Highlights: Distinction of PNES from epileptic seizures is of utmost clinical significance. Commonest semiology among Pediatric PNES was dialeptic. There was no significant correlation between semiology and stressors among children with PNES. In resource constrained settings, short term vEEG with induction can identify PNES. Abstract: Purpose: The current study was designed to analyze the clinical spectrum of Psychogenic non-epileptic seizures (PNES) in children. Methods: Children aged 6–16years with clinically suspected PNES, confirmed by short-term VEEG (STVEEGvideo electroencephalogram) and induction were classified as per Seneviratne classification. Stressors, associated co morbidities, Verbal IQ (Intelligence Quotient) and behavioral abnormalities were assessed using HTP(House tree person) test, DSM IV (Diagnostic and statistical manual of mental disorders) TR criteria, MISIC (Malin intelligence scale for Indian children) and CBCL (Child behaviour checklist). Results: Eighty children with PNES 45 boys; mean age: 10.5 (±1.6) years were enrolled. Median delay in diagnosis was 5 months IQR(interquartile range)- 0.5 to 48 months) and 45% patients were already on AEDs (antiepileptic drugs). Commonest semiology was dialeptic (42.5%), followed by mixed (28.8%), motor (15%) and nonepileptic aura (13.8%). Family stressors were the commonest followed by school related issues. The most common psychiatric comorbidity was adjustment disorder. Somatic complaints were observed in 50% children. Conclusions: Dialeptic PNES is commonest in children. In resource constrained settings, STVEEG along with induction is a reliable method to diagnose PNES. A comprehensive assessment protocol (including assessment of stressors) is needed for holistic management of pediatric PNES.